Revisiting community-based traditional irrigation systems in India - Kumar Gaurav; Prabhakar Sharma; Aviram Sharma (Heliyon)
Several scholars, policy think tanks and advocacy groups have advocated for reviving community-based traditional irrigation systems. Traditional irrigation systems are conceptualised as sustainable and resilient alternatives to large irrigation infrastructures. But do traditional irrigation systems always represent just, sustainable, and resilient alternatives? Based on interviews, focus group discussion, ethnographic fieldwork, and archival research, the paper offers a nuanced socio-historical understanding of one such community-based irrigation system, aka the ahar-pyne system of South Bihar, India. The paper revisits the idea of a community-based irrigation system as a just and sustainable alternative. The paper critiques the conventional and uncritical framing of the traditional irrigation system as a just alternative, employing insights from the STS (science, technology, and society) and critical social science literature on caste and community. While critiquing the traditional irrigation system, the paper explores the epistemic and socio-cultural challenges related to the governance of traditional irrigation systems in today's time.